An efficient decoupling dynamic algorithm for coupled multi-spring-systems. (15th October 2018) - Yuan, Peng; Li, Dejian; Cai, C.S.; Xu, Guoji
Highlights: The proposed method features with the second-order accuracy, adjustable dissipation, and same stability limit but higher accuracy compared to CDM. Only vector operations are required in the analysis for the problem with lumped mass and arbitrary damping matrics. Coupled multiple-spring-systems can be decoupled to independent multiple subsystems by using the proposed method. The simplification and efficiency in the calculation for the coupled system are presented by using the proposed method. Accurate results for the nonlinear problems can be obtained by using the proposed method. Abstract: In this paper, a novel explicit method for decoupling coupled multi-spring systems in the structural dynamic analysis is proposed by ensuring the second-order accuracy in the low-frequency domain. Two parameters μ and β are introduced in this method to flexibly adjust the stability and accuracy properties and suppress the high-frequency spurious vibrations in the solution. Firstly, the standard formulations of this method are derived and its stability and accuracy are analyzed through comparisons with other available state-of-the-art explicit methods in the literature. Then, the performance of this proposed method is specifically evaluated in terms of accuracy, dissipation in the high-frequency domain and computational efficiency, and effectiveness in dealing with nonlinearity through three examples. Finally, a vertical coupled multi-spring system, a train-rail-sleeper-ballast-bridge system, is employed to demonstrate the efficiency and decoupling properties of the proposed method. The presented attractive performance of this method illustrates its advantages in engineering applications.